Canine Fetal Peritonitis - de Assis, Andreia Regis; Feliciano, Marcus Antonio Rossi; Facco, Gilberto Gonçalves; Ishii, Patricia Eri; Martin, Cláudia Matsunaga; Fernandes, Carlos Eurico (Acta Scientiae Veterinariae, 2017)
Background: The occurrence of neonatal diseases and neonatal deaths in canines are considered higher in the first days of life of individuals and bacterial diseases are considered the second most common cause. Inflammation of the mesothelial lining of the abdominal cavity is referred peritonitis, which can be classified as primary or secondary and there is no description on the occurrence of canine fetal peritonitis in the veterinary literature. The objective of this study is to describe a case of canine fetus peritonitis, presenting abnormal sonographic findings of the fetus and abnormalities identified after birth that were not yet described in veterinary literature. Case: A female Poodle, six years of age, considered healthy and without clinical complications during the gestational period, was referred for sonographic evaluation at the end of the pregnancy, in order to evaluate of the fetal viability and estimate the gestational period. By ultrasound examination, two canine fetuses were identified and based on its morphogenesis and biparietal diameter, the estimated gestational age was approximately 58 days. On the individual examination of each of the fetus by ultrasound, it was found that one of them had normal sonographic findings and on the second canine fetus it was found an increase of the intra-abdominal echogenicity of tissues, loss of the sonographic definition of the intestinal loops and presence of laminar anechoic areas between the interfaces of organs, consistent with abdominal effusion. Parturition occurred the following day of the ultrasound examination no complications and with the birth of two canine fetuses. About six hours after birth, one of the neonates showed dyspnea, hypothermia, areas of ecchymosis, suffusion in the ventral abdominal region, icteric and pale mucous membrane and the presence of abdominal fluid and came to death about 30 min after. Cytological analysis of the sample revealed exuberant amount of erythrocytes, fibrin and leukocytes. Culture revealed infection by Staphylococccus aureus and Enterococcus sp. Presence of bloody fluid in the abdominal cavity was observed at necropsy, with yellowish parietal surface of the thoracic and abdominal cavities and petechiae on the lungs, heart, stomach surfaces and intestinal mucous membrane. Microscopically, the lungs showed extensive areas of parenchymal consolidation, vascular congestion and intense inflammatory infiltrate in the alveolar wall; the liver was characterized by vascular congestion, areas of degeneration of hepatocytes and presence of calcified foci, necrosis and inflammatory infiltrates. Associating the results and findings of the exams was possible to conclude the diagnostic of fetal peritonitis. Discussion: The visualization of abnormal findings in affected fetus by a gestational ultrasound exam makes this report inedited and relevant for veterinary obstetrics. This demonstrates the importance of ultrasound exam in pregnant bitches for early detection of maternal fetal diseases. Presence of abdominal fluid and increased mesenteric ochogenicity associated with loss of the intestinal loop definition corroborates with the clinical suspicion of peritonitis in fetus. Findings on the anatomopathological examination, cytology and culture allowed conclusion of the cause of death. Bacterial forms in the cytological smear supported the diagnostic suspicion of peritonitis. Gestational ultrasound exam performed in this report was essential for proper conduct of the pregnant bitch and viability of the fetuses, suggesting that the detected fetal abnormalities showed predictive value in the viability of diseased individual. This case report contributes with the description of canine fetal peritonitis.